Notes and new species of the Neotropical genus Nycterotis Felder, 1874 (Lepidoptera: Notodontidae, Nystaleinae) - V. O. Becker (SHILAP, 2020)
Four new species are described: Nycterotis lineata Becker, sp. n. and Nycterotis noelia Becker, sp. n., from Brazil, Nycterotis chaconi Becker, sp. n., from Costa Rica, and Nycterotis balcazari Becker, sp. n., from Guatemala. Nycterotis poecila Felder, 1874 and N. dognini (Draudt, 1932), are very closely related but distinct species.